Knowledge and Practice in Insulin Therapy in Patients with Diabetes Mellitus - Khan , Hasil; Khan, Kaleemullah; Khan, Aminullah; Fazal ur Rehman; Moneeb ur Rehman; Shah, Syed Nadir; Kakar, Sana Ullah (Indus Journal of Bioscience Research, 2024)
This study examines the knowledge, practices, and barriers affecting insulin therapy adherence in diabetes patients. Through a qualitative approach, semi-structured interviews were conducted with 100 participants currently on insulin therapy, with responses analysed thematically. Key findings highlighted four themes: healthcare support, psychological and social challenges, economic constraints, and knowledge gaps. While most participants demonstrated adequate knowledge of insulin administration and blood glucose monitoring, gaps were evident in insulin storage and injection site rotation, potentially impacting effectiveness. Psychological barriers such as injection anxiety, social stigma, and fear of long-term dependency significantly affected adherence. Additionally, financial burdens, especially among rural patients, and limited healthcare access were major obstacles. Findings emphasize the need for expanded support through education, counselling, and financial assistance to improve adherence. By addressing these barriers, healthcare providers can enhance diabetes management and patient outcomes.